Modified Atmosphere Packaging of Fish - A Review - T.K., Srinivasa Gopal; C.N., Ravishankar (Fishery Technology, 2025)
Shelf life and quality of fresh fish can be extended by the application of modified atmosphere packaging using high barrier packaging film and refrigerated storage. Modified atmosphere with high concentration of C02 inhibits or slows down the growth of various aerobic spoilage bacteria of fish products by extending the lag phase. It provides conditions for the growth of gram positive bacteria and food pathogens within the package. Major qualiy hazard is the risk of foodborne botulism. This paper reviews the literature relating to the scientific basis of these claims.